Proteo3Dnet: a web server for the integration of structural information with interactomics data. Issue Volume 49:Issue W1(2021) (8th May 2021) - Postic, Guillaume; Andreani, Jessica; Marcoux, Julien; Reys, Victor; Guerois, Raphaël; Rey, Julien; Mouton-Barbosa, Emmanuelle; Vandenbrouck, Yves; Cianferani, Sarah; Burlet-Schiltz, Odile; Labesse, Gilles; Tufféry, Pierre
Abstract: Proteo3Dnet is a web server dedicated to the analysis of mass spectrometry interactomics experiments. Given a flat list of proteins, its aim is to organize it in terms of structural interactions to provide a clearer overview of the data. This is achieved using three means: (i) the search for interologs with resolved structure available in the protein data bank, including cross-species remote homology search, (ii) the search for possibly weaker interactions mediated through Short Linear Motifs as predicted by ELM—a unique feature of Proteo3Dnet, (iii) the search for protein–protein interactions physically validated in the BioGRID database. The server then compiles this information and returns a graph of the identified interactions and details about the different searches. The graph can be interactively explored to understand the way the core complexes identified could interact. It can also suggest undetected partners to the experimentalists, or specific cases of conditionally exclusive binding. The interest of Proteo3Dnet, previously demonstrated for the difficult cases of the proteasome and pragmin complexes data is, here, illustrated in the context of yeast precursors to the small ribosomal subunits and the smaller interactome of 14–3–3zeta frequent interactors. The Proteo3Dnet web server is accessible at http://bioserv.rpbs.univ-paris-diderot.fr/services/Proteo3Dnet/ . Graphical Abstract: